Chapter Markets and Merchants: Commercial and Cultural Integration in Northwest Europe, 1300-1700 - Unger, Richard W (Atti delle «Settimane di Studi» e altri Convegni, 2019)
Between the thirteenth and seventeenth centuries commerce in northern Europe expanded and contracted. The long term net effect of the trade increase was an overall substantial impact on the economy and on the culture of the lands around the North and Baltic Seas. The development of interdependent markets can be indicated by examining the tendency of prices to converge in different places. Relying on previous research and novel ways of constructing indices using price data from a number of ports in northern Europe it is possible to confirm both the long term direction, with ups and downs, toward market integration as well as the emergence in the sixteenth and seventeenth centuries of regional markets in certain food grains.